Lo humano en la Antropología médica de A. Damasio - Miguel Grijalba Uche (Claridades: Revista de Filosofía)
The objective of this text is to define the concept that Antonio Damasio develops about man, the human and human intelligence. Antonio Damasio’s main thesis is the hypothesis of the cerebral subject, a neural and materialist image of man based on the brain. For Antonio Damasio, the human is understood in terms of a complex interaction between the body, the mind and the environment. To do this, three key notions that define this idea in Antonio Damasio are presented: emotional reflection, sentimental ethics and the gradualist theory of consciousness. This will converge in Damasio’s personal conception of intelligence, who emphasizes the importance of homeostasis in human intelligence. Our ability to adapt to the environment and make effective decisions is intrinsically linked to our ability to regulate our biological and emotional needs.